Peran Guru Dalam Menerapkan Pembelajaran Project Based Learning Pada Kurikulum Merdeka - Nadlir; Fitriyah, Afiyatul; sholihah, Laili Farichatus (Jurnal Ilmu Pendidikan dan Sosial, 2024)
The purpose of this study is to evaluate the implementation of the Project Based Learning (PjBL) model in subjects in the Merdeka Curriculum and its impact on student learning outcomes. This research used a descriptive qualitative approach to describe social phenomena. Primary data was obtained from structured interviews with a teacher at Madrasah Ibtidaiyah Lamongan, and secondary data from scientific journals and online sources. Data collection techniques included interviews, observation and documentation. Data analysis included asking questions, applying procedures, collecting, coding and interpreting data. This research aims to understand the meanings that individuals and groups ascribe to social or humanitarian issues. The research findings show that PjBL is effective in improving student learning motivation, team PjBL work skills, creativity, and understanding of basic concepts. Effective in increasing student learning motivation, teamwork skills, creativity, and understanding of basic concepts. To that end, PjBL also fosters enthusiasm and positive attitudes among students. However, PjBL research faces challenges such as high equipment requirements, high costs, and short lead times. Nevertheless, PjBL made a significant contribution to learning outcomes and the development of student characteristics according to the Pancasila Learner Profile